2014
DOI: 10.1093/gastro/gou017
|View full text |Cite
|
Sign up to set email alerts
|

Isolated pancreatic tuberculosis masquerading as pancreatic cancer

Abstract: Isolated pancreatic tuberculosis (TB) remains a rarity despite the high incidence of tuberculosis in many of the African and Asian countries. Presentation as discrete pancreatic mass often masquerades as pancreatic neoplasm and diagnosis may require histology. Extra-hepatic portal hypertension due to splenic vein thrombosis complicating pancreatic TB has been reported in the literature. We report here a case of isolated pancreatic TB with pancreatic head mass mimicking neoplasm with extra-hepatic portal hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Clinical and imaging findings may closely mimic pancreatic cancer and differential diagnosis may be difficult [77]. Abdominal pain, jaundice, and weight loss are the most common presenting symptoms in both clinical situations [78]. The disease may focally or Fig.…”
Section: Pancreatic Tuberculosismentioning
confidence: 99%
“…Clinical and imaging findings may closely mimic pancreatic cancer and differential diagnosis may be difficult [77]. Abdominal pain, jaundice, and weight loss are the most common presenting symptoms in both clinical situations [78]. The disease may focally or Fig.…”
Section: Pancreatic Tuberculosismentioning
confidence: 99%
“…38 Occasional reports have indicated that unusual complications like arterial pseudoaneurysms and extra-hepatic portal venous obstruction may occur in patients with pancreatic tuberculosis. 28,42,43 These may result in gastrointestinal bleeding related to pseudo-aneurysmal bleeding or gastric varices. 28,43 Magnetic resonance imaging has been occasionally used in evaluation of pancreatic tuberculosis.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…28,42,43 These may result in gastrointestinal bleeding related to pseudo-aneurysmal bleeding or gastric varices. 28,43 Magnetic resonance imaging has been occasionally used in evaluation of pancreatic tuberculosis. Magnetic resonance cholangiopancreatography may demonstrate dilatation of the bile and the pancreatic ducts because of obstruction by the tubercular pancreatic head mass.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…Pancreatic/parapancreatic TB is an uncommon form of abdominal infection and has a rare occurrence even in endemic regions. It accounts for less than 5% of all tuberculosis in the developing world [ 3 ]. Many epidemiological analyses suggest that the probability of tuberculosis is much higher among human immunodeficiency virus- (HIV-) positive people.…”
Section: Introductionmentioning
confidence: 99%